Traction Technique (Rajesh Rao’s) for Aortic Cannulation in Right Vertical Infra Axillary Thoracotomy - Rao, Rajesh Kishan; Preethi; Mehta, Sejal (International Journal of Innovative Research in Medical Science, 2025)
In minimally invasive cardiac surgery right vertical infra-axillary thoracotomy is one of the commonly used approach for repair of various congenital cardiac defects, valve repair or replacements, excision of myxomas. In this approach various cannulation strategies are followed depending on the patients profile and surgeon’s convenience. Aortic cannulation is easier in children and few adults. However, in adults with BMI more than 30kg/m2, aortic cannulation will difficult as aorta is far from thoracotomy. To bring aorta closer and stabilize, many surgeons apply long vascular clamps or right-angled forceps over epi aortic tissue. This not only compromises working space, also repeated application during cannulation and decannulation may cause injury. Here we describe a technique which is safe, atraumatic, do not compromise working space, brings aorta close and stabilizes the part of aorta during cannulation and decannulation. Overall, it provides a good control over aorta throughout the procedure.